Optimism and positivity biases in performance appraisal ratings: Empirical evidence from professional soccer - Merkel, S.; Chan, H. F.; Schmidt, S. L.; Torgler, B. (Applied Psychology, 2021)
Using unique assessment data for players from a German Bundesliga club`s youth academy, we tested four core hypotheses on how player ratings and rater or ratee-related characteristics reflect the (prospective) optimism bias and (retrospective) positivity bias. The results indicate not only that the ratings of predicted and remembered performance are indeed higher than the talents` actual performance throughout a season, but that these differences depend positively on the rater`s organizational experience and negatively on the amount of ratee data available. They also suggest that (prospective) anticipation is even more positively biased than (retrospective) recollection of player performances, underscoring the asymmetry between looking forward and looking backward.